Identification and Characterization of Differentially Expressed MicroRNAs in Benign Prostatic Hyperplasia - Lingmin Song; Xue Wang; Gang Wang; Liwei Zheng; Zhansong Zhou (Cancer Reports)
ABSTRACT Objectives The primary aim of this research is to identify and describe the distinct patterns of microRNAs (miRNAs) that are unusually expressed in benign prostatic hyperplasia (BPH) tissues compared to normal prostatic tissues. Materials and Methods The investigation began with the collection of three samples each from normal prostatic and BPH tissues. These samples underwent miRNA microarray analysis using the Agilent platform. Following the preliminary screening, a larger sample set, comprising five normal prostatic tissues and 36 BPH tissues, was subjected to qRT‐PCR to confirm the differential expression of the miRNAs initially identified. Results The microarray analysis revealed that only miR‐126‐3p and miR‐4672 exhibited an expression profile marked by both a fold change > 1.5 and p < 0.05, indicating significant downregulation in BPH tissues. MiR‐145‐3p and miR‐143‐3p also showed downregulation with fold changes greater than 1.5; however, these changes did not reach statistical significance as their p‐values were above 0.05. Further attempts to validate these findings through qRT‐PCR did not confirm any notable dysregulation among the four miRNAs studied; the variations in their expression levels between normal and BPH tissues did not achieve statistical significance, with p‐values exceeding 0.1. From the data accrued, it can be inferred that the roles of miR‐4672, miR‐126‐3p, miR‐145‐3p, and miR‐143‐3p in BPH development continue to be an unresolved mystery, and the need for further investigation. Conclusions This preliminary investigation establishes a foundation for subsequent studies aimed at elucidating the regulatory mechanisms underlying BPH. However, these results highlight the need for further investigation employing a more extensive sample size and comprehensive clinical data to elucidate their potential roles in the pathogenesis of BPH.